Implementation of the Basic Principles of State Administrative Justice in Ensuring Legal Certainty in Indonesia - Darwin Wibowo Sihombing; Fitri Amanda Hasibuan (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
The State Administrative Court (PTUN) plays an important role in the Indonesian legal system as a means of legal protection for the public against government actions. The existence of the PTUN is an implementation of the principles of the rule of law (rechtsstaat) and the rule of law, which emphasizes that every government action must be based on law and can be tested legally. The PTUN was established based on Law Number 5 of 1986 which has been amended through Law Number 9 of 2004 and Law Number 51 of 2009. In its implementation, the PTUN not only functions as an institution for resolving administrative disputes, but also as an instrument for monitoring the actions of public officials to prevent abuse of authority. This paper aims to explain the meaning of the main principles in the PTUN, identify the types of principles that apply, and analyze their application in the practice of state administrative justice. The method used is a normative approach by reviewing laws and regulations, legal doctrines, and related literature. The discussion results show that the basic principles of the PTUN, such as the presumption of justice, the principle of simple, fast, and low-cost justice, the principle of judicial objectivity, and the principle of transparency, play a fundamental role in ensuring justice, legal certainty, and the protection of citizens' rights. In practice, these principles serve as guidelines for examining, adjudicating, and deciding state administrative disputes. Therefore, the application of the basic principles of the PTUN is crucial for the effectiveness of administrative justice in realizing justice and controlling government actions.